Pengaruh Keragaman Dewan terhadap Kinerja Perusahaan (Studi Kasus Pada Bank Capital) - Bhenu Artha; Ali Jufri; Imam Hadiwibowo; Sinta Manggala (Universitas Muhammadiyah Ponorogo, 2021)
Financial performance is an analysis conducted to see the extent to which a company has implemented by using financial implementation rules properly and correctly. Company performance is a description of the financial condition of a company which is analyzed with financial analysis tools, so that it can be known about the good and bad financial condition of a company that reflects work performance in a certain period. This study aims to determine the effect of board diversity on company performance, especially Bank Capital for the period December 2012-December 2019. The results of the analysis show that there is no effect of board diversity on ROA and ROE at Bank Capital for the period December 2012-December 2019. There is no effect of board diversity on ROA and ROE. Bank Capital's performance is due to the percentage of female directors not reaching 50% in the board of directors so that their contribution does not have much influence on the company's strategic decisions.Keywords: Board Diversity, ROA, ROE